PELAYANAN SOSIAL LANJUT USIA BERBASIS SISTEM KEKERABATAN - Suradi, Suradi (Politeknik Kesejahteraan Sosial, 2006)
(Kinship System Based Old People Social Service) - Older peolpe in Indonesia keeps on rising from year to year. In 2020, it is predicted that there are about 28,8 milion older people or 11,34% of the total population. The rising of older population should not be worry if we create develop by government, social organization and kinship system. Therefore, we need an effort to revitalize social organization and make kinship system m local level mto mshtutlon m order to create synergy among those social service system.